How chinese auditors' relativistic ethical orientations influence their love of money - Woodbine, Gordon; Fan, Ying; Scully, Glennda (Business and Organization Ethics Network (BON), 2013)
Love of Money (LMOS) theory is well developed and widely used in studying people's beliefs about money (Luna-Arocas & Tang2004). This study examines the views of 612 Chinese auditors and establishes that the ideological positions adopted influence how they regard money and that these positions are related to underlying cultural norms. Forsyth's (1980) EPQis used to establish a viable model, which establishes that relativism strongly influences Chinese auditors" attitudes towards money and has important implications in terms of the impact on the accounting profession in that rapidly growing nation.